2014
DOI: 10.1016/j.ajpath.2014.07.017
|View full text |Cite
|
Sign up to set email alerts
|

The Membrane Attack Complex in Aging Human Choriocapillaris

Abstract: Age-related macular degeneration (AMD) is a common disease that can result in severe visual impairment. Abnormal regulation of the complement system has been implicated in its pathogenesis, and CFH polymorphisms contribute substantially to risk. How these polymorphisms exert their effects is poorly understood. We performed enzyme-linked immunosorbent assay (ELISA) analysis on young, aged, and AMD choroids to determine the abundance of the membrane attack complex (MAC) and performed immunofluorescence studies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 184 publications
(91 citation statements)
references
References 63 publications
(55 reference statements)
2
89
0
Order By: Relevance
“…Analysis of human donor eyes has shown that complement activation in the choroidocapillary region already starts early in life and is associated with choroidal thinning and the development of AMD [43]. In this study, it was shown that choroidal deposition of the MAC sC5b-9 in humans is already evident at the age of 5 years and that it increases during a lifetime.…”
Section: Complement Activation By Drusen Constituentsmentioning
confidence: 69%
“…Analysis of human donor eyes has shown that complement activation in the choroidocapillary region already starts early in life and is associated with choroidal thinning and the development of AMD [43]. In this study, it was shown that choroidal deposition of the MAC sC5b-9 in humans is already evident at the age of 5 years and that it increases during a lifetime.…”
Section: Complement Activation By Drusen Constituentsmentioning
confidence: 69%
“…Drusen are located on the RPE side of Bruch's membrane and complement is not only involved here but as shown recently also at the chorio-capillaris side [52]. Complement activation at the chorio-capillaris already starts early in life and is associated with choroidal thinning and development of AMD [54]. These authors showed that choroidal deposition of the membrane attack complex (sC5b-9) in humans was already evident at 5 years of age and that it increases markedly during life and with the presence of AMD.…”
Section: Pivotal Role Of Complement Activation In Amdmentioning
confidence: 96%
“…Quantitative analysis of sC5b-9 in retinal samples by ELISA showed that young donors had relatively low levels of sC5b-9. Retinal samples from AMD patients had variable but significantly higher sC5b-9 levels as compared to the age-matched control eyes [55]. Further support for a role of the complement system in AMD came from several genetic studies (see Table 2) that revealed that variants in complement system genes alter an individual's risk of developing AMD [56,57].…”
Section: Pivotal Role Of Complement Activation In Amdmentioning
confidence: 97%
“…Similarly, numerous clinical trials focused on targeting complement factors to prevent GA spread but were ultimately found ineffective. The biological relevance of CFH polymorphisms in and AMD context (Haines et al 2005;Edwards et al 2005;Klein et al 2005) remains elusive; Cfh mutant mice show only a marginal phenotype (Coffey et al 2007), and many individuals exhibiting complement deposition in the RPE never present with AMD (Anderson et al 2010;Mullins et al 2014). Thus, the field may be missing the biological understanding of AMD needed to create effective therapeutics.…”
Section: Perspectives On Future Directionsmentioning
confidence: 99%